Tourism in the slums of Rio de Janeiro: An analysis of the urban impacts in informal areas caused by recent public interventions for the big sports events hosted by the city - Rego Fagerlande, Sergio Moraes (International Planning History Society Proceedings, 2018)
The slums of Rio de Janeiro have been the stage of recent urban changes related to tourism-related activities, chiefly those linked to the large sports events such as 2014 FIFA World Cup, and the 2016 Olympic. The visiting by Brazilian and foreign people was always significant in the city, and the increase of the flow in the slums is a relevant fact. This article seeks to put the changes in the recent urban dynamics of those areas into perspective, as caused by popular settlements in which tourism has been bringing changes about, initially related to urban mobility, in the case of the large works done by the government. These interventions brought reflexes embodied in private and community-related investments, with the opening of hostels, bars and restaurants, along with the creation of new open spaces, such as parks and ecological trails. The work has been going on, with the mapping of these activities in the slums of Rio's South Zone, especially in the slum of Babilônia-Chapéu Mangueira, seeking data on their locations, and on the importance of community participation, and the relevance of public policies in the process at hand.